An Updated Perspective on Sinorhizobium meliloti Chemotaxis to Alfalfa Flavonoids - Compton, K. Karl; Hildreth, Sherry B.; Helm, Richard F.; Scharf, Birgit E. (Frontiers in Microbiology, 2020)
The symbiotic interaction between leguminous plants and their cognate rhizobia allows for the fixation of gaseous dinitrogen into bioavailable ammonia. The perception of host-derived flavonoids is a key initial step for the signaling events that must occur preceding the formation of the nitrogen-fixing organ. Past work investigating chemotaxis - the directed movement of bacteria through chemical gradients - of Bradyrhizobium japonicum, Rhizobium leguminosarum, and Rhizobium meliloti discovered chemotaxis to various organic compounds, but focused on chemotaxis to flavonoids because of their relevance to the symbiosis biochemistry. The current work sought to replicate and further examine Sinorhizobium (Ensifer) meliloti chemotaxis to the flavonoids previously thought to act as the principal attractant molecules prior to the initial signaling stage. Exudate from germinating alfalfa seedlings was analyzed for composition and quantities of different flavonoid compounds using mass spectrometry. The abundance of four prevalent flavonoids in germinating alfalfa seed exudates was at a ratio of 200:5:5:1 for hyperoside, luteolin, luteolin-7-glucoside, and chrysoeriol. Using quantitative chemotaxis capillary assays, we did not detect chemotaxis of motile S. meliloti cells to these and two other flavonoids identified in seed exudates. In support of these findings, the flavonoid fraction of seed exudates was found to be an insignificant attractant relative to the more hydrophilic fraction. Additionally, we observed that cosolvents commonly used to dissolve flavonoids confound the results. We propose that the role flavonoids play in S. meliloti chemotaxis is insignificant relative to other components released by alfalfa seeds.